Construction and Simulation of Online English Reading Model in Wireless Surface Acoustic Wave Sensor Environment Optimized by Particle Swarm Optimization - Bolan Zhou (Discrete Dynamics in Nature and Society)
English reading is an important way to consolidate and expand English language knowledge, and it is also an important way to obtain information and understand British and American culture. Therefore, reading teaching has always been an important part of English education and teaching at all levels and types of schools, and college English teaching is no exception. College English teachers have been carrying out teaching reflections in their reading teaching practice and constantly exploring teaching modes and teaching directions that improve students’ reading engagement and reading comprehension ability. However, the current daily teaching of English reading still generally maintains the traditional teaching mode. The entire reading learning process is monotonous, boring, and stylized, and the ability to acquire and process information cannot be combined with language knowledge and language skills. This kind of teaching mode severely inhibited the college students’ involvement in English learning model. Based on the electromagnetic-polarization response expression in a uniformly polarized half-space, this paper transforms the problem of polarization parameter extraction into a minimum optimization problem and constructs a fitness function. A set of polarization parameters is selected to calculate the electromagnetic-polarization response under trapezoidal waves in a uniform half-space, and the basic particle swarm algorithm is used to extract single and multiple parameters, respectively. In this paper, by adding a window to the test data in the time domain, the multiplicative and additive interference in the test signal is suppressed, and the signal-to-noise ratio of the test result is improved. We use the platform built in this article to wirelessly test the temperature characteristics of the surface acoustic wave sensor. The research results identified eight cognitive attributes of English reading and successfully generated diagnostic information at the group and individual levels and finally formed graphics and textual diagnostic feedback. There is a certain correlation between students’ vocabulary mastery and English reading performance, which shows that the vocabulary teaching method can help students better understand the reading materials and improve their reading performance. Combining two student interviews and learning logs, it can be seen that students’ understanding and frequency of use of vocabulary knowledge have increased significantly after the action research. It is generally recognized that vocabulary has a positive effect on improving reading level and can be based on the recognition and understanding of vocabulary. The mastery of vocabulary can promote the improvement of college students’ English reading level to a certain extent. Learners should strengthen vocabulary learning and face up to the importance of vocabulary knowledge in English reading.